Sinergi Kearifan Lokal dan Pendidikan Pondok Pesantren: Strategi Meredam Isu Ekstremisme di Madura - Hannan, Abd (Asketik: Jurnal Agama dan Perubahan Sosial, 2022)
This study examines the phenomenon of global extremism among the Madurese community and the strategy of resistance to it through the role and function of pesantren local wisdom education. There are three research problems examined in this paper; How is the religious reality among Islamic boarding schools in the midst of the issue of religious extremism in Madura? What is the attitude of the pesantren towards the emergence of the problem of religious extremism among the Madurese community? What is the role and function of pesantren local wisdom education in responding and responding to the growing issue of extremism among the Madurese community? Methodologically, this study is a qualitative study. There are two types of data used in the study, primary data sourced from the field and information media, both printed and online, as well as secondary data obtained from literature and previous studies. Based on the analysis of field data, this study finds that the religious reality in Madura in recent years has received attention as the involvement of a number of people in global terrorism networks has been revealed. Responding to this situation, it is necessary to take swift steps to counteract it. One of them is by maximizing the existence and role of pesantren. That Islamic boarding school education with local wisdom values embedded in it can be a protective fortress that can keep Madurese society away from the influences and teachings of global extremism. The value of local wisdom education here includes self-religious traditions that are inclusive, universal, and always uphold the principles of moderation such as fairness, balance, moderation, and tolerance.